Emapez’s Community Method for Fish Leather Dyeing - Laguna González, Carolina
The handcrafted work of the Colombian ethnic communities constitutes a fundamental element for the reconstruction and reparation of the victims of armed conflict. This work presents the experience of the women of the Emapez of Tumaco-Colombia community, who were victims of displacement and violence, and through their organization and productive force, have created a foundation for cooperative work. The work has generated transformative processes in the community through the recovery of ancestral artisan techniques, specifically in working with fish leather.